2007
DOI: 10.1161/circresaha.107.153650
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Cardiac Myosin-Binding Protein C and Cardiac Troponin I in the Myofibrillar Force Responses to Protein Kinase A Phosphorylation

Abstract: Abstract-The heart is remarkably adaptable in its ability to vary its function to meet the changing demands of the circulatory system. During times of physiological stress, cardiac output increases in response to increased sympathetic activity, which results in protein kinase A (PKA)-mediated phosphorylations of the myofilament proteins cardiac troponin (cTn)I and cardiac myosin-binding protein (cMyBP)-C. Despite the importance of this mechanism, little is known about the relative contributions of cTnI and cMy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
194
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(222 citation statements)
references
References 49 publications
(75 reference statements)
26
194
2
Order By: Relevance
“…Myofilament structure, arrangement, and function are thought to remain intact in skinned myocytes, as observed in studies in which these preparations were used to assess force development and relaxation. 18,21,44 Therefore, phosphorylation of cTnI under the conditions used here indicates that AMPK is capable of phosphorylating cTnI when assembled in the Tn complex and associated with other myofilament contractile proteins. Moreover, cTnI Ser149 was a target site under these conditions.…”
Section: Phosphorylation Of Ctni In Skinned Rodent Myocytesmentioning
confidence: 72%
“…Myofilament structure, arrangement, and function are thought to remain intact in skinned myocytes, as observed in studies in which these preparations were used to assess force development and relaxation. 18,21,44 Therefore, phosphorylation of cTnI under the conditions used here indicates that AMPK is capable of phosphorylating cTnI when assembled in the Tn complex and associated with other myofilament contractile proteins. Moreover, cTnI Ser149 was a target site under these conditions.…”
Section: Phosphorylation Of Ctni In Skinned Rodent Myocytesmentioning
confidence: 72%
“…Along these lines, Varian and Janssen [14] reported a frequency dependent decrease in myofilament sensitivity to Ca 2+ associated with increasing heart rates and most likely attributable to cTnI phosphorylation. The role of cTnI phosphorylation in the relaxant effect of adrenergic stimulation has also been emphasized in work reported by Stelzer et al [15] in studies of mice expressing cTnI-S23D/S24D against a cTnI and myosin binding protein C null background. These studies together with others provide compelling evidence for a prominent role of cTnI phosphorylation in the maintenance of power and frequency response in ejecting ventricles [13,[16][17][18][19].…”
Section: Specific Modifications In Troponin I Affect the Dynamics Andmentioning
confidence: 89%
“…MyBP-C is a substrate for PKA, PKC, and CamK II [7,14,15]. Phosphorylation of MyBP-C appears to be significantly involved in enhanced cross-bridge kinetics and therefore likely to be a significant functional mechanism along with TnI phosphorylation [16]. Phosphorylation of titin by PKA reduces passive tension [8].…”
Section: Changes To Myofilament Proteins and Molecular Mechanisms Of mentioning
confidence: 99%
“…For example, Wang and colleagues [90] used light and heavy acetic anhydride to differentially label TnI digests without and with PKC-b II treatment, and found that Thr144 could be phosphorylated by PKC-b II. Similarly, we used differential O 16 /O 18 labeling to quantify developmental phosphorylation changes and found three altered phosphorylation sites from LC2 and MyBP-C [104].…”
Section: Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation